2017
DOI: 10.3390/su9071161
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Reduction Potential of Resource-Dependent Regions Based on Simulated Annealing Programming Algorithm

Abstract: In recent years, developing countries, especially resource-dependent regions, have been facing the paradox of ensuring both emissions reduction and economic development. Thus, there is a strong political desire to forecast carbon emissions reduction potential and the best way to achieve it. This study constructs a methodology to assess carbon reduction potential in a resource-dependent region. The Simulated Annealing Programming algorithm and the Genetic algorithm were introduced to create a prediction model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The annealing algorithm generates a new solution space from the current solution [8]. In order to facilitate subsequent calculation and acceptance and reduce the time consumption of the algorithm, a new solution is usually selected from the simple transformation of the current new solution, such as replacing and exchanging all or part of the elements of the new solution [9]. The transformation method that generates the new solution determines the neighborhood structure of the new solution and therefore has a certain influence on the choice of cooling schedule.…”
Section: Introductionmentioning
confidence: 99%
“…The annealing algorithm generates a new solution space from the current solution [8]. In order to facilitate subsequent calculation and acceptance and reduce the time consumption of the algorithm, a new solution is usually selected from the simple transformation of the current new solution, such as replacing and exchanging all or part of the elements of the new solution [9]. The transformation method that generates the new solution determines the neighborhood structure of the new solution and therefore has a certain influence on the choice of cooling schedule.…”
Section: Introductionmentioning
confidence: 99%
“…It implies that strong leadership with rigid regulation on air pollution may lead the private sector to participate in a more effective manner. In the study to assess carbon reduction potential in the heavily resource-dependent Shanxi Province in China from 1990 to 2015, Li et al concluded that the carbon intensity could drop by 18.78% by 2020 [12]. This potential exceeds the 18% expectation of the Chinese government in its '13th Five-Year Work Plan' for controlling GHG emissions.…”
Section: Regulation Toward Green Technologymentioning
confidence: 90%
“…Unfortunately, this regulation on the carbon intensity of the province could further be reduce by 0.97 GHG ton per 10,000 yuan GDP. Due to this reduction on the local GDP, they suggested a flexible mechanism for reducing emissions, instead of the too strong and rigid regulation [12]. In order to examine the relationship between Beijing's urbanization efficiency and economic growth rate over time, Qi et al developed a comprehensive index system for assessing Beijing's economic growth rate and urbanization efficiency at the district (county) level for the period 2005-2014 [13].…”
Section: Regulation Toward Green Technologymentioning
confidence: 99%
See 1 more Smart Citation